New Method for Turning and Shutting Power Flow Light with Voice-Based Command Arduino Uno Using Smartphone - Yusmartato, Y; Lubis, Zulkarnain; Hasibuan, Abdurrozzaq; Krianto Sulaiman, Oris; Asaad, Mhd. (International Journal of Engineering and Technology, 2018)
Android provides an open platform for developers to create their own applications for use by a variety of devices, the purpose of this thesis to produce tangible results in providing comfort or ease of turning on the lights at home everyday without touching the switch, especially for physically disabled or difficult parents to stand. In making this thesis turn on the lights with arduino uno based voice command using smarthphone. The results achieved are to improve the comfort and convenience aspects for physically disabled or elderly people, difficult to stand or reach the light switch, where this tool can work after bluetooth device available dismartphone android. Basically the principle of user use this tool the user should be able to operate smartphone based on android operating system.Â